The Effect of Entrepreneurship Courses and Creativity Program on Students’ Interest in Entrepreneurship - Putri, Rahmah Dianti; Rahmawati, Fanni; Suroto, Suroto (FKIP Universitas Lampung, 2019)
The Effect of Entrepreneurship courses and Creativity Program on Students’ Interest in Entrepreneurship. Objectives: This study aims to determine the effect of Entrepreneurship courses and Student Creativity Program on the interest in entrepreneurship. Methods: Quantitative methods with regressionanalysis techniques (t-test) were used in this research involving 100 University of Lampung studentswho had attended Entrepreneurship courses and had participated in the Entrepreneurship StudentCreativity Program (Sampling). Findings: Based on the results of the t-test test it is known that, entrepreneurship courses (t: 3.768 / p <0.05) and student creativity program (t: 2.398 / p <0.05) can influence the interest in student entrepreneurship at Lampung University. The program have a positif effect on students interest in enterpreneurship.Keywords: Entrepreneurship, Student Creativity Program, Entrepreneurship Interest DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201910